Comparação de funções objetivo para seleção de PSS pelo amortecimento de oscilações em sistemas multimáquinas - Carbonera, Luis Felipe Bianchi (2015)
Small disturbances occur continuously in electrical systems mainly due to load and generation variations. This ends up causing low frequency voltage fluctuations that are usually observed in systems whose lines have weak connections. In addition to damaging loads connected to the same bus, they can even damage equipment and incurring in costs to the energy distributors. Moreover, such oscillations can resonate with the system parameters and cause a general collapse in energy supplies. In the literature, there are methods for the development of stabilizers for power systems that are implemented to counteract these perturbations. In this dissertation, we compared some objective functions and identified points that can be optimized for parameterization of power system stabilizers IEEE models: PSS2B, PSS4B and conventional Delta w PSS, by computer simulations. The adjustment methodology used in this dissertation is based on the genetic algorithm (GA) held in Simulink® with the aid of the Matlab toolbox Gatool®. The effectiveness of the suggested technique and stabilizers are checked using simulation results, where it is noticeable that the PSSs managed to dampen oscillations in almost all cases. The only one who did not realize the optimization was the Delta W PSS with ITSE objective function in the hydraulic turbine, which failed to dampen oscillations even for the best results. Moreover, it was also possible to notice that the same Delta W PSS with ITAE objective function had the best results for the two types of turbine.